Development of protocol for in vitro regeneration in Abelmoscus esculentus (L.) Moench (okra) through shoot apical meristem, and nutrient and biochemical composition of its leaves and fruits - Chika, Nwachukwu Emmanuel (2013)
Okra is an important vegetable of valuable nutrient, good sources of vitamins, important antioxidants and medicinal compounds such as polyphenols and gossypol. The tissue culture was carried out by using shoot apical meristem while the nutritional and biochemical values of fresh okra leaves and fruits were evaluated. Meristematic tissues (0.4 -0.6mm) of okra seedlings were excised. Shoot apical meristems (SAM) were cultured in MS medium supplemented with a range of concentrations of NAA (0.1 mg/l 0.5mg/l, BAP (0.1mg/l, 2- 4.0mg/l), and in combination of NAA and BAP (0.1 mg/l – 1.0mg/l). This present study showed the highest shoot proliferations and formation from SAM on semi-solid MS medium cultured on 1.5mg/l BAP with four shoots per culture and best rooting on 1.0mg/l with an average of 4 roots per culture. The plantlets were transferred into pots containing soil for acclimatization and showed average of 82% survival. The proximate analysis was used to determine the percentage of protein, carbohydrate, ash, fats, fiber and moisture present in okra leaves and fruits. In addition, selected biochemical properties of okra leaves and fruits such as Chlorophyll a, b, xanthophylls and caretonoids, total phenolics and total flavonoids were measured spectrophotometrically. This study revealed the highest percentage of protein (4.82%) and ash (2.44%) in okra leaves while fruits contain highest percentage carbohydrate (11.17%), crude fiber (2.44%) and moisture (88.47%). Interestingly, this present study found that okra leaf contains higher chlorophyll, total phenolics and total flavonoid than okra fruit. Okra leaf showed highest chlorophyll a (23.66mg/0.1g), carotenoids (4.63mg/0.1g), Chlorophyll b (6.6mg/0.1g). Furthermore, the result also showed highest total phenolics (0.99mg/ 0.1g) and flavonoids (0.80mg/0.1g) in the leaf. This study has established standard protocol for in vitro regeneration of mucilaginous plant such as okra and okra leaf has shown to contain high nutritional and biochemical value compared with okra fruit.